Endometriosis classification according to pain symptoms: can the ASRM classification be improved?. (August 2018) - Andres, Marina Paula; Borrelli, Giuliano Moysés; Abrão, Mauricio Simões
Abstract: Endometriosis is a chronic disease that affects 5–15% of women of the reproductive age. Different classifications systems have been proposed to categorize endometriosis. In 1979, the American Fertility Society proposed a new system for the classification of endometriosis to correlate surgical findings of endometriosis with fertility, and this system was revised in 1996 (rASRM). Despite the fact that the rASRM classification system is widely used and accepted worldwide, it has limitations. The objectives of this study were to critically assess and discuss the current classification of endometriosis according to pain.